Burning mouth syndrome: A discussion about possible etiological factors and treatment modalities - Nakazone, Paula Aparecida [UNESP]; Nogueira, Andressa Vilas Boas; de Alencar Júnior, Francisco Guedes Pereira; Massucato, Elaine Maria Sgavioli [UNESP] (My University, 2009)
Although several studies discuss the contributing factors associated with the burning mouth syndrome (BMS), there is still controversy with regard to its etiology. Therefore, in the majority of cases, the establishment of an adequate diagnosis and consequently the best treatment modality is complicated. In order to assist the clinician in the establishment of the correct diagnosis and management of BMS, this article reviews the literature, providing a discussion on the various etiologic factors involved in BMS, as well as the best treatment modalities for this condition that have showed to be the most effective ones in randomized clinical trials. In addition, the authors discuss some clinical characteristics in the differential diagnosis of BMS and other oral diseases. It is important for the clinician to understand that BMS should be diagnosed only after all other possible causes for the symptoms have been ruled out.
Keywords: Burning mouth syndrome; Mouth diseases; Xerostomia